Proteomic profiling of saliva reveals association of complement system with primary Sjögren's syndrome. Issue 4 (13th September 2021) - Li, Mingde; Qi, Yajun; Wang, Guizhen; Bu, Su; Chen, Ming; Yu, Jiahui; Luo, Tianyang; Meng, Lulu; Dai, Anran; Zhou, Yong; Liu, Shuai; Huo, Xingxing
Abstract: Introduction: To compare the saliva proteomes of experimental Sjögren's syndrome (ESS) model mice and healthy controls to identify potential diagnostic biomarkers for primary Sjögren's syndrome (pSS). Methods: Proteins were extracted from the saliva of three ESS and three normal control mice using the data‐independent acquisition technique. R language was used to identify the differentially expressed proteins (DEPs). Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses were performed to functionally annotate the DEPs. The protein–protein interaction (PPI) network was constructed and the core proteins were identified with the STRING website and Cytoscape software. The concentrations of Serpin family G member 1 (SERPING1), C3, complement factor H (CFH), fibrinogen alpha (FGA), and fibrinogen gamma (FGG) in saliva were determined by ELISA. Results: A total of 1722 DEPs were identified in the saliva of the ESS mice relative to the controls, of which 50 showed significantly different expression levels between the two groups. SERPING1, C3, CFH, FGA, and FGG were significantly downregulated, and keratin 4 (Krt4) and transglutaminase 3 (TGM3) were upregulated in the saliva of ESS mice. The PPI network showed that SERPING1, C3, FGG, FGA, TGM3, and hemopexin (HPX) were the core proteins. ELISA results showed that the expression of C3, CFH, FGA, and SERPING1 were significantly downregulated in the saliva of ESS mice. However, the expression of FGG was a little downregulated but with no significant difference. SERPING1, FGG, and FGA may downregulate the complement C3 by inhibiting immune complement system, thereby promoting pSS progression. Conclusions: The salivary proteome of ESS mice was markedly different from that of healthy controls, suggesting that salivary proteomics is a promising noninvasive diagnostic tool for pSS. SERPING1, C3, CFH, FGA, and FGG are potential biomarkers of pSS. Abstract : To summarize our findings, Serpin family G member 1 (SERPING1), C3, fibrinogen alpha (FGA), fibrinogen gamma (FGG), and complement factor H (CFH) were significantly decreased in the saliva of ESS model mice and may therefore be potential diagnostic biomarkers of pSS. The role of these proteins in pSS and other autoimmune diseases (especially systemic lupus erythematosus) will have to be verified in experimental and cohort studies before possible applications in clinical diagnosis and treatment.